Fine mapping of ZNF804A and genomime-wide significant evidence for it's involvement in Schizophrenia and bipolar disorder. - GILL, MICHAEL; CORVIN, AIDEN; MORRIS, DEREK; QUINN, EMMA (My University, 2011)
A recent genome-wide association study (GWAS) reported evidence for association between rs1344706 within ZNF804A (encoding zinc-finger protein 804A) and schizophrenia (P=1.61 × 10(-7)), and stronger evidence when the phenotype was broadened to include bipolar disorder (P=9.96 × 10(-9)). In this study we provide additional evidence for association through meta-analysis of a larger data set (schizophrenia/schizoaffective disorder N=18 945, schizophrenia plus bipolar disorder N=21 274 and controls N=38 675). We also sought to better localize the association signal using a combination of de novo polymorphism discovery in exons, pooled de novo polymorphism discovery spanning the genomic sequence of the locus and high-density linkage disequilibrium (LD) mapping. The meta-analysis provided evidence for association between rs1344706 that surpasses widely accepted benchmarks of significance by several orders of magnitude for both schizophrenia (P=2.5 × 10(-11), odds ratio (OR) 1.10, 95% confidence interval 1.07-1.14) and schizophrenia and bipolar disorder combined (P=4.1 × 10(-13), OR 1.11, 95% confidence interval 1.07-1.14). After de novo polymorphism discovery and detailed association analysis, rs1344706 remained the most strongly associated marker in the gene. The allelic association at the ZNF804A locus is now one of the most compelling in schizophrenia to date, and supports the accumulating data suggesting overlapping genetic risk between schizophrenia and bipolar disorder.
PUBLISHED
PMID: 20368704
Keywords: Psychiatry; Schizophrenia; Genes & Society; Neuroscience